Non-Invasive Pulse Wave Analysis in a Thrombus-Free Abdominal Aortic Aneurysm after Implantation of a Nitinol Aortic Endograft - Georgakarakos, Efstratios; Argyriou, Christos; Georgiadis, George S.; Lazarides, Miltos K. (Frontiers in Surgery, 2016)
Endovascular Aneurysm Repair has been associated with changes in arterial stiffness, as estimated by pulse wave velocity (PWV). This marker is influenced by the medical status of the patient, the elastic characteristics of the aneurysm wall and the intraluminal thrombus. Therefore, in order to delineate the influence of the endograft implantation in the early postoperative period, we conducted non-invasively pulse wave analysis in a male patient with an abdominal aortic aneurysm of no intraluminal thrombus, no medical history and absence of peripheral arterial disease. Central systolic and diastolic pressure decreased postoperatively. PWV showed subtle changes from 11.6m/sec to 10.6 and 10.9 at 1-week and 1-month, respectively. Accordingly, the augmentation index decreased from 28% to 14% and continued to drop to 25%. The augmentation pressure decreased gradually from 15- to 6- and 4mmHg. The wave reflection magnitude dropped from 68% to 52% at 1-month. Finally, the peripheral resistance dropped from 1.41 to 0.99 and 0.85 dyn×sec×cm−5. Our example shows that the implantation of an aortic endograft can modify the wave reflection in aorta without causing significant alterations in PWV.